IMPLEMENTATION OF MORAL LEARNING THROUGH MORNING HABITUATION ACTIVITIES AT SMP MUHAMMADIYAH 6 SURAKARTA - Ariana, Erina Friesca; Khuriyah, Khuriyah (Jurnal Al Burhan, 2024)
The problem taken from this research is that it can be seen from the negative impact of students using social media, resulting in a gradual decline in the morals of students who are disrespectful to their parents, teachers, and social environment. Other negative activities that are commonly done include playing online games with friends for too long, YouTube, watching Korean movies, and other forms of entertainment that waste time. One of the activities that can fortify students from the influence of social media is the morning habit at SMP Muhammadiyah 6 Surakarta. This is different from schools where there is no implementation of morning habituation. Therefore, this study aims to examine moral learning through morning habituation activities at SMP Muhammadiyah 6 Surakarta. In this study, researchers used qualitative research with a phenomenological approach. Data collection techniques using observation techniques. The results showed that the application of moral learning was carried out in a hide curriculum and fostered good habits in the form of time discipline, the process of reading the Qur'an, dhikr, and dhuha prayers as well as improving reading the Qur'an and procedures for prayer and ablution for students.